Principle of uniformity under the CISG: opportunities and threats - Rohozianska, Daria (Riga Graduate School of Law, 2023)
The present thesis examines the principle of uniformity under Art. 7(1) of the United Nations Convention on Contracts for the International Sale of Goods. The problem of the present research is that while the CISG is a successful attempt of unification and harmonization of international sales law, still there are some obstacles to its practical implementation, such as differences between authentic texts of the CISG, and the absence of the supranational court to interpret it. Thus, the objectives are firstly, to determine the exact threats, secondly to conclude from this, and third, under the concrete example of Ukraine as the CISG’s contracting state to illustrate how the CISG could become an opportunity if it is interpreted and applied under its international character and the need to promote uniformity. As a result, the CISG could work as a tool for the development.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International private law and international procedural law; CISG; The United Nations Convention on Contracts for the International Sale of Goods; uniformity